Towards an integrative framework of leadership development in the South African banking industry - Jivan, Ajay Manhur (My University, 2019)
The thesis is a qualitative, multi-site case study of leadership development within the South African retail banking sector. It responds to the call for qualitative research to explore and give voice to the South African and other developing contexts within the predominantly Western-centric literature. It poses questions on the day-to-day organisational and lived realities of leadership and its development within this context. It is an enquiry of the forms and realities of aligning, designing and integrating leadership development, which leads to deliberation on the possibility of integrative frameworks. This follows from the thesis drawing together the reviews of the state of leadership and leadership development and how the thematic of alignment and integration is approached therein and within the human resource, management and organisational literature. Through this it develops an argument that the mainstream assumptions and programme-based approach to leadership development, including the remedial attempts to address this, do not provide the space to theoretically and empirically attend to, and engage with, the realities, complexities, contingencies and contestations at the individual, team, organisational, sector, national and global levels. The thesis explores this within the South African retail banking sector. This is done through qualitative interviews on, and thematic analysis of, the various mandates, purposes, funding and ways of configuring and managing leadership development within the banks’ Leadership Development Centres and the Banking Sector Education and Training Authority’s (BankSeta) International Executive Development Programme (IEDP) which is hosted at a local Business School. The thesis explores how leadership development is formalised, shaped, configured and managed as a function, purpose, programme and developmental process within the above sites, and how these are navigated, negotiated, enacted and embodied over time by the various stakeholders. It draws out the thematic of layered journeys; that is, the evolving and ongoing organisational, programmatic, pedagogic, personal and individualised journeys within the banks, BankSeta and the Business School. The journeys illustrate how leadership development evolves, opens up and differentiates over time at the different sites and levels as well as foregrounds the realities, complexities, contingencies and contestations therein. Through these journeys one appreciates the varied forms, perspectives, basis, sites, agency and spaces for designing and integrating leadership development and how these evolve, including how the standardisation, tailoring and customisation evolves. The deliberate, emergent, contingent and relational nature of designing and integrating, and the journey’s thematic, point to the limits of the mainstream assumptions and programme-based approach to leadership development. The thesis suggests a critical theoretical stance as an alternative as it provides space to critically attend to, engage with, and undertake the journey, task and process of aligning, designing, integrating and managing leadership development. It proposes ways to locate this task and process within the integrative theoretical models of leadership and the fields of instructional design, curriculum design and design of artefacts as well as the literature on the evolving human resources function, the identity work therein, and on space and place. It then suggests an organising model that can serve both as a guide for developing an open, modular platform and an analytical framework. In this way, the thesis contributes to the question and task of integrative frameworks of leadership development. Keywords: context, post-Apartheid, banking, leadership, leadership development, alignment, design, customisation, integration, pedagogy, journey, programme, function, centre, modular, platform
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, South Africa, in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, South Africa, in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD)
Keywords: Leadership--South Africa; Banks and banking--South Africa; Bank management--South Africa